ACTUAL PROBLEMS OF PROFESSIONAL AND PERSONAL DEVELOPMENT QUALIFIED PERSONS RESPONSIBLE FOR QUALITY OF MEDICINAL PRODUCTS FOR HUMAN USE - Zh. I. Aladysheva; N. V. Pyatigorskaya; V. V. Belyaev; N. S. Nikolenko; E. I. Nesterkina; S. A. Loseva (Фармация и фармакология (Пятигорск), 2021)
The aim of the study is to investigate topical problems of the professional and personal development of qualified persons responsible for quality of medicinal products for human use.Materials and methods. In the period from April 6 to May 10, 2020, an online survey of leading employees in the field of quality assurance of Russian manufacturers was conducted. 176 people took part in the survey; the return of questionnaires was about 17.9%.Results. From the standpoint of D. Super’s theory of professional development, the largest number of respondents was at the maintenance stage, holding their achieved positions (53.2%). All respondents, regardless of age, were motivated for professional development. Most often qualified persons had chemical engineering (27.3%) and pharmaceutical education (22.2%). Most of them had a working experience in 1–2 divisions of the enterprise, and combined the functions of qualified persons with managerial positions (74.5% and 71.9%, respectively). The majority of the qualified persons (86.4%) indicated the sufficiency of the available knowledge and the lack of knowledge on certain issues. Knowledge and skills in the quality risk management, specific GMP issues and statistical methods (59.0%, 49.2 and 44.2%, respectively); communication and interpersonal skills and, in particular, stress management, emotion management and the art of negotiation (49.4%, 41.3% and 40.9%, respectively), were most popular. About 36% of respondents notified the need for the digital economy competencies, while only 5.1% notified the presence of an electronic batch production record at the enterprise. Finally, only half of the respondents (50.5%) had a formal training plan for qualified persons.Conclusion. This pilot study revealed the need for the revision of the Exemplary Additional Professional Training Program for Qualified Persons and the professional standard, the urgent need for the regulatory body to develop a scheme and principles for the continuous professional development of qualified persons, and showed the direction of further research in this area.